A bleeding heart: case report and review of pericardial angiosarcoma - Ujjwal Madan; Himil Mahadevia; Parth Sharma; Satya Preetham Gunta; Ossama Tawfik; Karen Fritchie; Julian Magadan (University of São Paulo, 2024)
Primary cardiac tumors are rare. The cardiac sarcomas are the most common malignant cardiac tumors. These tumors have a dismal prognosis with an overall median survival of 25 months. Clinical features include dyspnea, arrhythmias, pericardial effusions, heart failure, and sudden cardiac death. The diagnosis is often challenging. Therefore, the cardiac imaging workup plays a central role in addition to a high clinical suspicion in the setting of atypical presentations that do not respond to standard therapies. The echocardiography, computed tomography, and cardiac MRI are crucial in clinching the diagnosis. Multimodal treatment with surgery, chemotherapy, and radiotherapy has been shown to improve outcomes, as opposed to using either of these modalities alone. We describe the case of a 30-year-old gentleman with COVID-19 infection who developed recurrent hemorrhagic pericardial effusions refractory to standard treatment and was eventually diagnosed as a case of pericardial angiosarcoma after his biopsy revealed the diagnosis and staging was performed using PET-CT-FDG scan. Our case re-emphasizes the importance of considering a malignant etiology early in the course of the disease presentation, especially in recurrent hemorrhagic effusions despite an inflammatory cytologic diagnosis of fluid. It also highlights the place for cardiac CT and MRI to ascertain the location and spread and to plan the further course of treatment. If diagnosed early, the estimated survival time can be prolonged by instituting a multimodal approach.